Analysis of Artificial Intelligence Policies for Higher Education in Europe. - M. Stracke, Christian; Griffiths, Dai; Pappa, Dimitra; Bećirović, Senad; Polz, Edda; Perla, Loredana; Di Grassi, Annamaria; Massaro, Stefania; Prifti Skenduli, Marjana; Burgos, Daniel; et al. (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
This paper analyses 15 AI policies for higher education from eight European countries, drawn from individual universities, from consortia of universities and from government agencies. Based on an overview of current research findings, it focuses the comparison of different aspects among the selected AI policies. The analysis distinguishes between four potential target groups, namely students, teachers, education managers and policy makers. The paper aims at contributing to the further development and improvement of AI policies for higher education through the identification of commonalities and gaps within the existing AI policies. Moreover, it calls for further and in particular evidence-based research to identify the potential and practical impact of AI in higher education and highlights the need to combine AI use in (higher) education with education about AI, often called as AI literacy.